2007
DOI: 10.1159/000110455
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Toll-Like Receptor 4 in Neuroinflammation in Alzheimer’s Disease

Abstract: Microglial activation is a key feature in Alzheimer’s disease and is considered to contribute to progressive neuronal injury by release of neurotoxic products. The innate immune receptor Toll-like-receptor 4 (TLR4), localized on the surface of microglia, is a first-line host defense receptor against invading microorganisms. Here, we show that a spontaneous loss-of-function mutation in the Tlr4 gene strongly inhibits microglial and monocytic activation by aggregated Alzheimer amyloid peptide resulting in a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
369
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 472 publications
(385 citation statements)
references
References 46 publications
(51 reference statements)
10
369
0
6
Order By: Relevance
“…For example animal models of AD and patients with AD exhibit increased expression of CD14, (a co-receptor for TLR4), TLR4 and TLR2 [33][34][35][36], which are thought to occur independently in response to the presence of Aβ. Interestingly a polymorphism in TLR4 Asp299Gly resulted in a 2.7 fold reduction in risk for late onset AD [37].…”
Section: Role For Tlrs In Alzheimer's Diseasementioning
confidence: 99%
“…For example animal models of AD and patients with AD exhibit increased expression of CD14, (a co-receptor for TLR4), TLR4 and TLR2 [33][34][35][36], which are thought to occur independently in response to the presence of Aβ. Interestingly a polymorphism in TLR4 Asp299Gly resulted in a 2.7 fold reduction in risk for late onset AD [37].…”
Section: Role For Tlrs In Alzheimer's Diseasementioning
confidence: 99%
“…It is well described that TLR4 is involved in neurodegeneration 12, 14. It was also found that TLR4‐dependent microglial activation mediates spinal cord ischemia–reperfusion injury 11.…”
Section: Resultsmentioning
confidence: 95%
“…TLR3 also causes downregulation of TLR4 17. TLR4 has been shown to trigger neuronal degeneration and to be involved in several kinds of neurological disorders 12, 14, 15. TLR3 activation with the synthetic RNA analogue poly(I:C) and simultaneous TLR4 downregulation have been described as protective against ischemia– reperfusion injury of the spinal cord 11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations